Analysis of gait characteristics to evaluate injury risk after high-intensity exercise, focusing on canoe athletes: a preliminary study - Kim, Seoungeun; Son, Minji; Shin, Seungmin; Kim, Taewan; Choi, Seungjun (Frontiers in Sports and Active Living, 2025)
ObjectiveHigh-intensity exercise can alter gait characteristics in canoe athletes, potentially affecting performance and increasing injury risk due to muscle fatigue. This study aimed to analyse gait parameters before and after high-intensity exercise to identify fatigue-related injury risk factors.MethodsTwelve canoe athletes participated. After a brief treadmill acclimation (30–60 s), gait was assessed at three walking speeds: slow (80%), normal (100%), and fast (120%) of preferred speed—for 1 min each. An IMU based shoe-type data logger captured gait data immediately before and after a 30 s Wingate Anaerobic Test.ResultsSignificant changes were found in 20 gait parameters. Post-exercise, cadence, stride/step length, single/double support time, time of toe off, ankle ROM (dorsiflexion/plantarflexion, inversion/eversion), and centre of gravity (COG) displacement and velocity in X and Y directions increased. In contrast, COG displacement, velocity, and acceleration in the Z direction decreased.ConclusionGait analysis at slow speed after high-intensity effort highlights the importance of monitoring biomechanical and spatiotemporal changes. Detecting compensatory gait adjustments post-exercise may enable early identification of fatigue-related injury risks, supporting preventive strategies for canoe athletes.